Diversidade Cultural: um olhar pela perspectiva de professores de Educação Física Escolar - Souza, Cristiane Pereira de (2022)
This research composes a doctoral thesis presented to the Graduate Program in Education (PPGE) of the Federal University of São Carlos (UFSCar), inserted in the line of research School Education: theories and practices. The question answered in this study was: What contributions do the teaching/res of School Physical Education in the first and second years of elementary school promote the understanding of Cultural Diversity? Its objective was to identify and analyze what contributions the teachers of School Physical Education offer to the treatment/approach/inclusion of the theme of Cultural Diversity in the school from what they do within the classes. This research addressed the problem of Cultural Diversity within School Physical Education, signaling the importance of new research in this field of knowledge, highlighting the triangulation among: Teachers, School Physical Education and Cultural Diversity, which corroborates the need for teachers to reflect on pedagogical practices that privilege Cultural Diversity, questions and discussions, within the school environment. The methodology adopted is qualitative in nature, with a questionnaire as data collection instruments and the execution of five focus group meetings. We have the collaboration of 15 teachers from municipal and state public schools in the State of São Paulo, Minas Gerais and Espírito Santo as participants of the research. We performed data analysis with precepts of content analysis, with which we obtained the following categories: Teachers/res: Who are they/ them? Meanings attributed to cultural diversity and cultural diversity and its scope in School Physical Education. The theoretical framework was based on the works of Paulo Freire. The main results obtained were: the teachers/res through their cultural identities attribute meanings to Cultural Diversity through cultural identity, difference and differences and specificities of Physical Education. We identified that Cultural Diversity manifests itself for these teachers/res through the social markers of difference: ethnic-racial relations, politics, religion and gender and sexuality.